SISTEM PENUNJANG KEPUTUSAN KENAIKAN GOLONGAN PADA SMA LAKSAMANA MARTADINATA DENGAN MENERAPKAN BAHASA PEMROGRAMAN JAVA - Ahir Yugo Nugroho Harahap (STMIK KAPUTAMA, 2019)
Decision Support Systems (SPK) are designed to support all stages of decision making starting from identifying problems, selecting relevant data, determining the approach used in the decision making process, to evaluating alternative choice